Diagnostic Efficacy of grey-zone Serum Prostate Specific Antigen level in patients with Benign Prostatic Hyperplasia and Prostate Carcinoma - Syed Atif Hussain; Rukhsana Tumrani; Afsheen Nigar; Anber Rahim; Mahnoor Chaudhry; Seerat Fatima Tu Zahra (Journal of Bahria University Medical and Dental College, 2025)
Objective: Evaluation of diagnostic role of grey zone serum prostate specific antigen level(4-10ng/ml) in patients with benign prostatic hyperplasia (BPH) and prostate carcinoma keeping histopathology as gold standard. Study design and setting: Cross-sectional study conducted in department of urology and chemical pathology, sheikh Zayed hospital Rahim yar khan.